The association between substance abuse, psychosis and activity participation in adults: a retrospective record review - Nepaul, Qulinta (My University, 2017)
Background: Co‐morbid substance abuse and psychotic disorders result in decreased activity participation. However, the association between substance abuse and activity participation in psychotic disorders has not been explored. In this study, the activity participation on admission and discharge were compared between Substance Induced Psychosis (SIP) and Schizophrenia without substance abuse. Methodology: A quantitative, descriptive, retrospective case study design with correlations was used. A database with demographic information and activity participation assessments of mental health care users (MHCUs) was used. Descriptive quantitative analysis, correlations and effect sizes was used to analyse the data. Results: The largest age groups for the SIP group were the 20 to 29 and 30 to 39‐year‐old cases. Activity participation scores for both groups showed impaired functioning on the creative ability level of Self‐presentation, with changes after intervention from patient‐directed to the transitional phase for the SIP group and therapist‐directed to patient‐directed phase for the Schizophrenia group. In terms of cognitive functioning, the Schizophrenia group improved by one phase, for Process skills, matching the SIP group on discharge. Conclusion: Activity participation is impaired in SIP but also in Schizophrenia without substance abuse. Concerning demographic data showed the prevalence of substance abuse in young adults and the disruptions of employment. Effect sizes showed clinically small changes but noteworthy improvements, as MHCUs move closer to independence.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Occupational Therapy. Johannesburg, 2017.
Keywords: Psychotic Disorders; Schizophrenia; Substance-Related Disorders